New Trends in China's Educational Diplomacy under the "Belt and Road" Initiative----- Case study of China's higher education policy in Pakistan (Journal of Interdisciplinary Insights, 2024)
With the promotion of the "One Belt, One Road" initiative and the increasingly frequent exchanges and cooperation between China and the rest of the world, education, culture, economy, and other emerging elements are gradually taking center stage in diplomatic talks. China and Pakistan's educational cooperation is based on the fact that the two countries are friendly neighbors with a long tradition of friendship. It has been 70 years since educational cooperation between China and Pakistan began in 1955 and reached new heights. In the context of the "One Belt, One Road" and the China-Pakistan Economic Corridor projects, China's education diplomacy has progressed in a solid and orderly manner, and the two countries have made significant achievements in international student education activities, building educational cooperation business cards and academic research platforms. There are still many differences between the two countries in terms of higher education philosophy and cooperation management planning, and there is still great potential for improving the education cooperation between China and Pakistan. This paper discusses the new path and significance of China's educational diplomacy in Pakistan, analyses the advantages and disadvantages of educational cooperation between the two countries, and proposes a new approach suitable for China's educational diplomacy according to the situation of both countries.